Characterization of critical flux in a submerged membrane bioreactor system - Halim, Kinski Komaneci (2009)
Membrane bioreactor (MBR) systems have been widely used as a replacement to secondary clarifier in wastewater treatment plants. However, membrane fouling and its consequences in terms of plant and maintenance costs limit the application of MBRs. To mitigate this problem, industry often operates at sub-critical fluxes. Such a practice links to the concept of critical flux which is defined as the flux below which there may be no fouling of the membrane. Various experimental methods for measuring critical flux and the effect of time intervals and pressure stepping intervals were studied. The results clearly showed that different experimental methods provide different accuracy for critical flux determination. Both time intervals and pressure stepping interval were also found to cause different level of membrane fouling.